SHIELDING AND MASKING PROPERTIES OF THE METAMATERIAL AS SCREENS - S. F. Ali (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of the significant channels of information leakage can be radio emission of information source. Channel protection against leakage of information can be provided by shielding the source of information, or by ensuring the secrecy of the object information leakage for direction finding and radar systems. These directions can be realized through the creation of devices based on impedance or dissipative screens. We consider the electromagnetic impedance screens for screening facilities are sources of emissions and improving stealth location of such facilities. The properties of flat, parabolic, cylindrical and conical screens closed and open type.